1998
DOI: 10.1006/anbo.1998.0712
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variability in Differential Expression of lea2 and lea3 Genes and Proteins in Response to Salinity Stress in Fingermillet (Eleusine coracanaGaertn) and Rice (Oryza sativaL.) Seedlings

Abstract: Some late embryogeny abundant (LEA) proteins, which are developmentally regulated in embryos, are also known to be expressed in meophytic tissues in response to osmotic stress. Here we report the extent of genetic variability in the level of expression of lea2 and lea3, under stress, in fingermillet and rice seedlings. In both species, the expression of lea genes was seen in the mesophytic tissue in response to salinity, partial dehydration and abscisic acid. Tolerant genotypes exhibited higher expression of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 23 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…The genotypic variability in differential expression of lea genes and proteins in response to salinity stress was noticed by Jayaprakash et al (1998) in finger millet (Eleusine coracana) and rice (Oryza sativa L.) seedlings. In analogy, in our present study the LEA 3 expression was found higher in both mulberry cultivars subjected to salinity stress treatments, besides there is a marked difference in the expression levels of LEA 3 in the two genotypes with higher level of expression in S1 than in ATP (Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…The genotypic variability in differential expression of lea genes and proteins in response to salinity stress was noticed by Jayaprakash et al (1998) in finger millet (Eleusine coracana) and rice (Oryza sativa L.) seedlings. In analogy, in our present study the LEA 3 expression was found higher in both mulberry cultivars subjected to salinity stress treatments, besides there is a marked difference in the expression levels of LEA 3 in the two genotypes with higher level of expression in S1 than in ATP (Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…DHNs are localized in various subcellular compartments, including cytosol (Roberts et al, 1993), nucleus (Houde et al, 1995), chloroplast (Artus et al, 1996), vacuole (Heyen et al, 2002), and proximal to the plasma membrane and protein bodies (Asghar et al, 1994;Egerton-Warburton et al, 1997;Puhakainen et al, 2004). Elevated expression of Dhn genes generally has been correlated with the acquisition of tolerance to abiotic stresses such as drought (Whitsitt et al, 1997), salt (Godoy et al, 1994;Jayaprakash et al, 1998), chilling (Ismail et al, 1999a), or freezing (Houde et al, 1995;Danyluk et al, 1998;Fowler et al, 2001). The differences in expression and tissue location suggest that individual members of the Dhn multigene family have somewhat distinct biological functions (Close, 1997;Zhu et al, 2000;Nylander et al, 2001).…”
mentioning
confidence: 99%
“…Several other studies in different species demonstrated that upon acclimation in seedlings as well as plants, significant increase in HSPs (HSP 70, HSP 104, HSP 90 and HSP 18.1) occurred (Uma et al 1995;Kumar et al 1999;Srikanthbabu et al 2002;Senthil-Kumar et al 2003). The importance of acquired thermotolerence in crop plants under heat stress was reported by several authors (Uma et al 1995;Jayaprakash et al 1998;Kumar et al 1999;Burke et al 2000;Burke 2001;Srikanthbabu et al 2002;Senthil-Kumar et al 2003;2007).…”
Section: Introductionmentioning
confidence: 85%